Comment le travail journalistique amplifie la hiérarchie de genre. Une rédaction pendant la campagne présidentielle de 2012 - Séverine Chauvel; Amélie Le Renard (Genre, Sexualité et Société)
The ethnographic observation of a national daily newspaper's editorial staff during the presidential election campaign of 2012 reveals that, in spite of the anti-sexist remarks expressed by several journalists during their daily work and during interviews,the conditions under which information is produced amplify gender hierarchy between candidates. Our hypothesis is that of an intertwining of professional standards on the one hand, which leave little place for reflexivity on gender issues, and the constraints of contemporary journalistic work on the other, which requires quasi-instantaneous treatment of information, in a context of strong competition between medias. The article analyses the hierarchies and the exercise of authority within the editorial staff, the way urgent work is distributed and the ordinary expressions of anti-sexist consciousness in an environment where "political neutrality" is required. This contextualization allows one to better understand three characteristics of the campaign treatment in the media: the relative invisibilization of female candidates; the differentiated treatment of most female politicians; the over-representation of male (activists or voters) among visible persons in newspapers.